Different hydrogel architectures synthesized by gamma radiation based on chitosan and N, N-dimethylacrylamide. (23rd April 2018) - Tinoco, D.; Ortega, A.; Burillo, G.; Islas, L.; García-Uriostegui, L.
Abstract: Abstract : The present work focuses on the radiation-modification of chitosan (CS) with N, N-dimethylacrylamide (DMAAm) presented as three different architectures: comb-type grafting hydrogels ( net- CS)-g-DMAAm, interpenetrating networks of CS and DMAAm ( net- CS)-inter-( net -DMAAm), and semi-interpenetrating networks ( net- DMAAm)-inter-CS. The syntheses of different polymeric architectures were realized by gamma irradiation by a 60 Co source. The optimum conditions for the syntheses of the three systems were at a dose of 6 kGy. Only the comb-type system presented a well-defined critical pH. All the hydrogels showed porous and interconnected structures according to scanning electronic microscopy. These different architectures could be used as three-dimensional cell culture scaffolding.